2018
DOI: 10.1016/j.redox.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbonylation on glutathione peroxidase-1 activity in human hyperglycemic endothelial cells

Abstract: AimsHigh levels of glucose and reactive carbonyl intermediates of its degradation pathway such as methylglyoxal (MG) may contribute to diabetic complications partly via increased generation of reactive oxygen species (ROS). This study focused on glutathione peroxidase-1 (GPx1) expression and the impact of carbonylation as an oxidative protein modification on GPx1 abundance and activity in human umbilical vein endothelial cells (HUVEC) under conditions of mild to moderate oxidative stress.ResultsHigh extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 61 publications
(83 reference statements)
1
15
0
1
Order By: Relevance
“…On the other hand, when mussels were contaminated the decrease of LPO levels under tidal regime may indicate that the limited presence of MWCNTs, only during high tide periods, caused a less stressful condition or the combination of air exposure and MWCNT contamination induced higher oxidative stress compared to organisms submersed the entire experiment in the presence of these which was surpassed by the activation of NPs antioxidant enzymes that eliminated ROS and prevented the occurrence of LPO. (Sultan et al, 2018). In fact, ROS may promote the oxidation of proteins, a process known as protein carbonylation (PC) which constitutes the most common type of PTM triggered by oxidative stress (Cattaruzza and Hecker, 2008;Suzuki et al, 2010 In general, the present results showed no alteration on PC levels in ).…”
Section: Oxidative Damagesupporting
confidence: 41%
“…On the other hand, when mussels were contaminated the decrease of LPO levels under tidal regime may indicate that the limited presence of MWCNTs, only during high tide periods, caused a less stressful condition or the combination of air exposure and MWCNT contamination induced higher oxidative stress compared to organisms submersed the entire experiment in the presence of these which was surpassed by the activation of NPs antioxidant enzymes that eliminated ROS and prevented the occurrence of LPO. (Sultan et al, 2018). In fact, ROS may promote the oxidation of proteins, a process known as protein carbonylation (PC) which constitutes the most common type of PTM triggered by oxidative stress (Cattaruzza and Hecker, 2008;Suzuki et al, 2010 In general, the present results showed no alteration on PC levels in ).…”
Section: Oxidative Damagesupporting
confidence: 41%
“…The hindering mechanisms act through the poly-ADP-ribose polymerase (PARP) pathway, which alters GAPDH through polymers of ADP-ribose. Hyperglycemia provokes overproduction of ROS [ 99 ] and DNA single-strand cracks [ 100 ], both of which can stimulate PARP [ 101 ], thereby resulting in an alteration of GAPDH and a decrease of its activity [ 102 ] ( Figure 2 ).…”
Section: Diabetes and Oxidative Stressmentioning
confidence: 99%
“…In the mitochondrial matrix, superoxide dismutase (SOD) 2 reduces O 2 − into H 2 O 2 , a less toxic ROS [83]. Then, glutathione peroxidase (GPX) catalyzes the reduction of H 2 O 2 into H 2 O through the oxidation of reduced glutathione (GSH) into its oxidized form (GSSG) [84,85]. Catalase in the mitochondrial matrix can also convert H 2 O 2 into water and molecular oxygen [86,87].…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%